Effects of Developmental Care on Neurodevelopment of Preterm Infants - Soleimani, Farin; Azari, Nadia; Ghiasvand, Hesam; Fatollahierad, Shiva (Iranian Journal of Child Neurology, 2020)
Abstract Objectives The aim of this study protocol is to systematically review the literature to examine the effects of developmental care on preterm infants’ neurodevelopment in the neonatal intensive care unit (NICU). Methods: We will retrieve the studies through searching the following databases: Web of Science, PubMed, EMBASE (Ovid), Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL (EBSCO), and Scopus. We will include randomized controlled trials (RCTs) with randomization at either an individual or cluster level. Our primary outcome will be the effect of developmental care in NICU neonates on their mental and motor development. The secondary outcome will be weight gain in NICU and hospital stay length. The assessment tool of development should be The Bayley Scales of Infant and Toddler Development, in any of the first, second and third edition. This study will employ Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to identify relevant articles and report the screening process. The agreement between two experts in developmental neonatology will be reached in all selecting studies. Two reviewers will be achieved data extraction and then they will be compared. Any discrepancies between the extracted data will be discussed to reach a consensus. The extracted data will be imported to Review Manager 5.3 by one reviewer. Two reviewers will independently evaluate the risk of bias for all included studies using the Cochrane Collaborations’ tool for assessing risk of bias in randomized trials. We will conduct a meta-analysis for assessing the possible quantitative impact of developmental interventions on interested primary and secondary outcomes. We will use random effect if the I-square statistics is equal or more than 75%, and fixed effect otherwise. Publication bias will be assessed using Egger’s test and illustration with the funnel plot. We will estimate the Standardized Mean Difference (SMD) with 95% confidence interval through Metan command in STATA 14. The method provided by the Cochrane hand book, will be used in this statistical analysis. The significance level for assessing these analyses will be 0.05. Discussion: According to the findings of this systematic review, by abstracting the results and presenting the conclusions, improvements in interventional decisions can be improved, and results of this systematic review will highlight which clinical practice could possibly be optimized to improve outcome and specifically neurodevelopment in this vulnerable population.